Comparing Surgical Treatments for Spondylolysis: Review on Current Research. Issue 8 (October 2021) - Tarpada, Sandip P.; Kim, Dongyoung; Levine, Nicole L.; Morris, Matthew T.; Cho, Woojin
Abstract : Study Design: Narrative review. Objective: To compare the various surgical methods of repairing spondylolysis defects in regard to improving pain, restoration of function, radiographic improvement, and complication rate. Summary of Background Data: Spondylolysis is a defect in the pars interarticularis of the vertebral arch, typically in the lumbar vertebra. Treatment can be nonoperative and/or surgical. There are various types of surgical repair including spinal compression, fusion, and direct pars repair. Methods: A comprehensive review of the English literature was performed utilizing Medline, Embase, and Web of Science. Inclusion criteria included papers or abstracts that evaluated the surgical techniques. Exclusion criteria included non–English-language papers or abstracts with inadequate information about outcomes. Results: Postoperative pain levels and patient function were consistently improved, regardless of surgical technique chosen. Positive clinical outcomes after surgery were seen more often in patients under age 20 and those who underwent minimally invasive repairs. Positive radiographic improvements were reported broadly, although some reported higher rates of nonunion with spinal compression. Complication rates were low throughout and minimally invasive techniques reported decreased blood loss and shorter hospital stays. Conclusions: Present surgical options appear largely comparable in terms of their ability to provide meaningful treatment for spondylolysis where conservative treatments have failed or otherwise remain unattempted.